Arbitrarily primed polymerase chain reaction-based identification of dystrophic onychomycosis - Sandeep Kaur (Archives of Medicine and Health Sciences, 2020)
Background and Objective: Onychomycosis is a fungal infection of the nails; when caused by dermatophytes, it is called as Tinea unguium. The aim was to explicate the utility of arbitrarily primed polymerase chain reaction (AP-PCR) to augment the early and accurate clinical diagnosis of dystrophic onychomycosis. Materials and Methods: The collected nail samples were divided into three portions. The first portion was explored for direct microscopic examination, the second portion was used for culturing of the nail samples on sabouraud dextrose agar media, and the third portion was used for DNA extraction followed by AP-PCR identification of dermatophytes. Results: All 48 samples with dystrophic onychomycosis were diagnosed by three methods, namely, 20% Potassium hydroxide microscopy, culture growth, and AP-PCR. With all the methods, Trichophyton rubrum was found as major causative agents for dermatophyte nail infection (60%), followed by Trichophyton mentagrophytes (23% cases). AP-PCR is a convenient method to achieve a higher dermatophyte identification rate with lesser time and shows complete concordance with conventional culture for two Trichophyton species. Conclusion: AP-PCR is a rapid, specific, and sensitive procedure for the diagnosis of nail fungal infection.